2020
DOI: 10.1097/aln.0000000000003263
|View full text |Cite
|
Sign up to set email alerts
|

An Effective and Efficient Testing Protocol for Diagnosing Iron-deficiency Anemia Preoperatively

Abstract: Background Iron-deficiency anemia is a common perioperative condition and increases perioperative morbidity and mortality. Timely diagnosis and treatment are important. This retrospective cohort study tested the hypothesis that a newly developed preprocedure evaluation protocol diagnoses more patients with iron-deficiency anemia than the traditional practice of obtaining a complete blood count followed by iron studies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…4 Efficient testing protocols to identify patients who can benefit from IV iron preoperatively in 1 clinic visit have been described. 11 Despite its safety and efficacy, recommendations on when to give iron infusions vary. Currently, the American Society of Anesthesiologists Task Force recommends preoperative erythropoietin with or without iron to reduce intraoperative allogeneic blood transfusions and the administration of iron to patients with IDA only if time permits.…”
Section: Discussionmentioning
confidence: 99%
“…4 Efficient testing protocols to identify patients who can benefit from IV iron preoperatively in 1 clinic visit have been described. 11 Despite its safety and efficacy, recommendations on when to give iron infusions vary. Currently, the American Society of Anesthesiologists Task Force recommends preoperative erythropoietin with or without iron to reduce intraoperative allogeneic blood transfusions and the administration of iron to patients with IDA only if time permits.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that blood transfusions are associated with postoperative complications such as infections, need for intensive care and prolonged hospital length of stay [14,15]. In fact, the severity of anemia is directly correlated with worse outcomes, such as the likelihood of readmission ing protocol, the pre-procedure anemia evaluation (PPAE), was implemented in January 2017, and has been shown to effectively and efficiently diagnose anemia including IDA [30], thereby allowing for expedited treatment (Figure 1). The PPAE order set includes reflex anemia testing when a hemoglobin concentration is less than or equal to 12 g/dL on the complete blood count.…”
Section: Anemiamentioning
confidence: 99%
“…The PPAE order set includes reflex anemia testing when a hemoglobin concentration is less than or equal to 12 g/dL on the complete blood count. Although the World Health Organization defines anemia as a hemoglobin less than 13 g/dL for men and less than 12 g/dL for women [42], we had designed the hemoglobin trigger for reflex testing on our PPAE at 12 g/ dL or lower to simplify the process [30]. The diagnostic tests in the reflex testing evaluate the different etiologies of anemia and include reticulocyte count, serum iron concentration, transferrin saturation, serum ferritin concentration, total iron-binding capacity, thyroid-stimulating hormone concentration, creatinine concentration, estimated glomerular filtration rate and vitamin B 12 concentration.…”
Section: Anemiamentioning
confidence: 99%
See 2 more Smart Citations